Impacts of Digital Technologies on Child and Adolescent Health: Recommendations for Safer Screen Use in Educational Settings - Cullen, J; Muntz, A; Marsh, S; Simmonds, L; Mayes, J; O’neill, K; Duncan, S (Pasifika Medical Association Group, 2024)
The use of screen-based digital technologies (such as computers and digital devices) is increasing for children and adolescents, worldwide. Digital technologies offer benefits, including educational opportunities, social connection and access to health information. Digital fluency has been recognised as an essential skill for future prosperity. However, along with these opportunities, digital technologies also present a risk of harm to young people. This issue may be particularly important for young New Zealanders, who have among the highest rates of screen use in the world. Our recently published review examined the impacts of digital technologies on the health and wellbeing of children and adolescents. Key findings revealed some positive impacts from moderate use of digital technologies; however, frequent and extended use of screen-based digital tools were associated with negative impacts on child and adolescent health in some areas, such as eye health, noise-induced hearing loss and pain syndromes. Conversely, in areas such as mental health, wellbeing and cognition, quality of screen media content and additional factors such as age may be more important than duration of use. These challenges gave us the impetus to develop pragmatic recommendations for the use of digital technologies in schools, kura kaupapa and early childhood education. Recommendations include interventions to lower risk across different ages and stages of development. Supporting young people to mitigate risk and develop safer screen behaviours will allow them to gain essential digital skills and access opportunities that will enable them to thrive.
Keywords: 4203 Health Services and Systems; 32 Biomedical and Clinical Sciences; 42 Health Sciences; Pediatric; Prevention; Generic health relevance; 3 Good Health and Well Being; 11 Medical and Health Sciences; General & Internal Medicine; 32 Biomedical and clinical sciences; 42 Health sciences; Adolescent; Child; Humans; Adolescent Health; Child Health; Digital Technology; New Zealand; Schools; Screen Time; Adolescent; Child; Humans; Adolescent Health; Child Health; Digital Technology; New Zealand; Schools; Screen Time